MATHEMATICS IN ART: HISTORY AND MODERNITY - Маслюченко, Володимир Кирилович; Маслюченко, Галина-Жанна Ярославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The role of mathematics in art, in particular, in the project of modern Ukrainian artist Svyatoslav Virsta (Chernivtsi), "Ia formula" is analyzed.